Effects of experimental perturbation of group structure on hierarchy formation and behaviour in House Sparrows - Robin J. Kubitza; Jukka Suhonen; Timo Vuorisalo (BirdLife Finland, 2022)
Establishment of dominance hierarchies has been proposed as amechanism that stabilizes andmaintains social groups by reducing physical intra-group conflicts. However, the exact behavioural processes involved in hierarchy formation within natural populations, as well as those leading to destabilization, are still a matter of debate. Here, we investigate possible behavioural processes in play during periods of high and low social cohesion by experimentally manipulating group structure (experimental perturbation). House Sparrows (Passer domesticus) are an ideal study species as they form gregarious flocks structured by social dominance. Using a non-breeding flock of wild-caught urban sparrows, we analysed four behavioural parameters (outside the feeding context: agonistic behaviour; within the feeding context: non-aggressive joining, aggressive supplanting and the duration of feeding bouts) in relation to birds’ sex and social rank during successive periods of unstable and stable group structure. In this population birds established a hierarchy quickly after initial group fusion but did not re-establish transitive relationships after a subsequent perturbation of group structure. Dominant birds consistently showed more frequent agonistic and supplanting behaviour than subordinates, irrespective of experimental condition. Likewise, the length of feeding boutswas unaffected by the experimental treatment. Thus, House Sparrows appear to be resilient to a certain degree to disruptions of social organization. However, female but not male House Sparrows selectively increased rates of non-aggressive joining during the latter period of social stability. Here, we highlight processes involved in the formation and re-formation of social hierarchies in natural populations that are exposed to frequent sources of instability.